THE GIG ECONOMY AND THE SOCIAL CONTRACT: RETHINKING LEGAL, TRAINING, AND ENGAGEMENT STRATEGIES FOR CONTINGENT WORKERS - Marhamah; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2026)
The rapid expansion of the gig economy has significantly altered traditional employment relationships, challenging existing assumptions about the social contract between workers and organizations. As contingent work becomes more prevalent, gaps have emerged in legal protections, training opportunities, and engagement practices. This study examines how the social contract must be redefined to address these challenges, with a particular focus on legal, training, and engagement strategies for gig workers. Using a conceptual and narrative literature review approach, the research synthesizes insights from academic studies, policy reports, and industry analyses. The findings indicate that traditional labor frameworks are insufficient for managing gig work, necessitating legal reconfiguration to balance flexibility with worker protection. Additionally, training and development are increasingly decentralized, requiring shared responsibility among workers, organizations, and institutions. Engagement strategies must also evolve, leveraging digital tools, incentives, and transparent communication to build trust and inclusion. The study highlights the importance of collaboration among stakeholders to ensure fairness and sustainability in gig work systems. It concludes that redefining the social contract is essential for aligning organizational efficiency with worker well-being. The article provides a comprehensive framework for adapting workforce strategies in the evolving gig economy.